2012
DOI: 10.1161/strokeaha.112.661793
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Prevents Progression for Cognitive Impairment and Vascular Dementia

Abstract: Background and Purpose-We aimed to study if physical activity could interfere with progression for cognitive impairment and dementia in older people with white matter changes living independently. Methods-The LADIS (Leukoaraiosis and Disability) prospective multinational European study evaluates the impact of white matter changes on the transition of independent elderly subjects into disability. Subjects were evaluated yearly during 3 years with a comprehensive clinical protocol and cognitive assessment with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 34 publications
2
69
1
2
Order By: Relevance
“…67 Physical activity reduces the risk of cognitive impairment, mainly vascular dementia, in older people living independently. 148 There is also evidence that exercise has positive effects on depression 149 and cognition 150 in adults without stroke, and there are preliminary findings that exercise may confer similar effects after stroke. 18,21 Although few studies have investigated the impact of fitness training on cognition and mood after stroke, a recent report 21,151 using combined aerobic and resistance training noted improvements in overall cognition and in the subdomains of attention/concentration and visuospatial/executive function.…”
Section: Cardiovascular Cognitive and Functional Outcome Measuresmentioning
confidence: 99%
“…67 Physical activity reduces the risk of cognitive impairment, mainly vascular dementia, in older people living independently. 148 There is also evidence that exercise has positive effects on depression 149 and cognition 150 in adults without stroke, and there are preliminary findings that exercise may confer similar effects after stroke. 18,21 Although few studies have investigated the impact of fitness training on cognition and mood after stroke, a recent report 21,151 using combined aerobic and resistance training noted improvements in overall cognition and in the subdomains of attention/concentration and visuospatial/executive function.…”
Section: Cardiovascular Cognitive and Functional Outcome Measuresmentioning
confidence: 99%
“…It has been demonstrated that patients benefit from recommendations of physical exercise. 39 They may also benefit from cognitive rehabilitation training 40 and pharmacological therapy with acetylcholinesterase inhibitors. 41 …”
Section: Strokementioning
confidence: 99%
“…At the end of the 3-year Leukoaraiosis and Disability study, 90 of the 639 participants had developed dementia. 21 Physical activity (at least 30 minutes of activity on at least 3 days per week) significantly reduced the risk of cognitive impairment, especially vascular dementia. In a large, racially diverse cohort of 876 older adults (the Northern Manhattan Study), there was more likely to be decline at 5 years in semantic memory and executive function if there were low levels of leisure time physical activity.…”
Section: Healthy Eating and Regular Exercise To Prevent Dementiamentioning
confidence: 99%